2007
DOI: 10.1007/s10897-006-9067-y
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Self‐Reported Personal History of Cancer in an Outpatient Breast Center

Abstract: The self-reporting of cancer history is becoming increasingly important, as it frequently guides medical decision-making. We studied the accuracy of personal cancer history using a self-administered questionnaire, comparing the results with the Tumor Registry at our institution. Among 39,662 records, we identified 3614 women with a single cancer in the Tumor Registry who reported none or one cancer on their questionnaire. The sensitivity in self-reporting cancers was 85.7%, ranging from 92.1% for breast cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
11
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 18 publications
3
11
1
Order By: Relevance
“…The high consistency of the information observed for cancer status (92.59%), cancer type (85.33%) and age of onset of cancer (92.64%) in FDRs is comparable to figures reported in a few previous studies from the USA [8,35,36]. Regarding relationship to the proband, one of the most interesting results was the high consistency of the information about cancer diagnoses in mothers (95%).…”
Section: Discussionsupporting
confidence: 83%
“…The high consistency of the information observed for cancer status (92.59%), cancer type (85.33%) and age of onset of cancer (92.64%) in FDRs is comparable to figures reported in a few previous studies from the USA [8,35,36]. Regarding relationship to the proband, one of the most interesting results was the high consistency of the information about cancer diagnoses in mothers (95%).…”
Section: Discussionsupporting
confidence: 83%
“…Accuracy of self-reported cancer history validated against medical records and cancer registry data has been found to be high [29], with high sensitivity in cancer outpatient samples [30]. …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, even though eliciting a family history is crucial, its accuracy cannot be assured. Multiple studies have shown that patient recall of their family history is often inadequate (Dominguez et al, 2007; Gaff et al, 2004; Glanz et al, 1999; King et al, 2002; Mai et al, 2011; Murff et al, 2004; Ozanne et al, 2012; Pinsky et al, 2003; Quillin et al, 2006; Weinrich et al, 2002; Wideroff et al, 2010; Ziogas & Anton-Culver, 2003) and can vary by education level (Wideroff et al, 2010), income (Weinrich et al, 2002), race (Dominguez et al, 2007; Pinsky et al, 2003; Wideroff et al, 2010), gender (Glanz et al, 1999; Pinsky et al, 2003; Wideroff et al, 2010) and cancer site of origin (King et al, 2002; Mai et al, 2011; Murff et al, 2004; Ziogas & Anton-Culver, 2003). Asking patients to report their family history before the genetic counseling session provides an opportunity for the patient to confer with relatives and gather information, allowing for more comprehensive and accurate family history collection.…”
Section: Introductionmentioning
confidence: 99%